2005
DOI: 10.1007/s00339-005-3404-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrode surface treatment and electrochemical impedance spectroscopy study on carbon/carbon supercapacitors

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in: http://oatao.univ-toulouse.fr/ Eprints ID : 2600 ABSTRACT Power improvement in supercapacitors is mainly related to lowering the internal impedance. The real part of the impedance at a given frequency is called ESR (equivalent series resistance). Several contributions are included in the ESR: the electrolyte resistance (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(95 citation statements)
references
References 26 publications
4
87
1
Order By: Relevance
“…Electrochemical impedance spectroscopy is an important technique to characterize the electrochemical frequency behavior of a device, and the obtained data are generally plotted in a Nyquist diagram that represents the imaginary part of the impedance vs. the real part (Taberna et al, 2006). Figure 6 exhibits the Nyquist plot for two ZIC cells assembled with liquid-and gel-electrolyte.…”
mentioning
confidence: 99%
“…Electrochemical impedance spectroscopy is an important technique to characterize the electrochemical frequency behavior of a device, and the obtained data are generally plotted in a Nyquist diagram that represents the imaginary part of the impedance vs. the real part (Taberna et al, 2006). Figure 6 exhibits the Nyquist plot for two ZIC cells assembled with liquid-and gel-electrolyte.…”
mentioning
confidence: 99%
“…Therefore, different sized pores in a porous electrode will have different time constants, which can be correlated to electrolyte ion access times, as elaborated by LozanoCastello [17] and others [7,14,24]. The implication is that not all of the accessible surface area of a porous electrode can be accessed within the same time frame and the maximum capacitance will depend upon the density of the charging current or modulating frequency [4,9,12]. The diffusion rates of ions into and within the different sized pores will vary with the frequency, which directly impacts the response times of the double-layers established on the surfaces of those accessed pores.…”
Section: Electrochemical Impedance Spectroscopy Analysesmentioning
confidence: 95%
“…The degree of rectangularity in a CV is an indication of how close the performance of a supercapacitor approaches that of an ideal capacitor: the more rectangular the CV, the more the supercapacitor cell approaches capacitor-like behavior. Additionally, it is understood that the average of the absolute values of the charging current and the discharging current is representative of the total capacitance for the cell [4,14]. A capacitance value for the cell can therefore be calculated from the CV data by integrating the current over the entire CV curve and obtaining an average value.…”
Section: Cyclic Voltammetry (Cv) Measurementsmentioning
confidence: 99%
“…[9][10][11] The ESR, is a collective measure of all kinds of resistances contributed by various sources present in the supercapacitors that include the resistance of current collector; the interfacial resistance between the electrode material and the currentcollector; electronic resistance of the electrode material; the ionic (diffusion) resistance of ions transporting through smaller pores; the ionic resistance of ions moving through the separator; and the electrolyte resistance. [9][10][11] The power density of the supercapacitor can therefore be increased either by increasing the potential or by reducing the ESR. Higher potential can be controlled by modifying the electrolyte properties, 12,13 while a lower ESR value can be achieved by reducing the internal resistance of the electrode and the contact resistance between the electrodes and the current collectors.…”
Section: Introductionmentioning
confidence: 99%
“…Higher potential can be controlled by modifying the electrolyte properties, 12,13 while a lower ESR value can be achieved by reducing the internal resistance of the electrode and the contact resistance between the electrodes and the current collectors. 9 It has been observed that supercapacitors with low ESR values can be fabricated by modifying aluminium current collectors with carbon material via sol-gel and coating, 11 modifying aluminium current [15][16][17][18][19][20][21][22][23][24][25][26] Studies on the modification of separators have also been reported elsewhere. 27,28 Recently, the low ESR value has been achieved by modifying the SS current collector by the deposition of platinum nanoparticles, wherein the modified current collector was tested in supercapacitor cell fabricated with activated carbon monolith (ACM) electrode derived from rubber wood saw dust.…”
Section: Introductionmentioning
confidence: 99%